DAMPAK SEMINAR DAN WORKSHOP ACCURATE TERHADAP MINAT BELAJAR SOFTWARE AKUNTANSI - Erikson Damanik (Politeknik Bisnis Indonesia, 2018)
The purpose of this study is to determine the impact of seminars and workshops on the interest of learning softwarre accounting. This research was conducted at Polytechnic of Bisnis Indonesia Pematangsiantar with sample size of 48 students with the determination of the number of samples based on purposive sampling technique, the method used is associative (relationship) which aims to know the relationship between two variabe or more. The analysis technique used is multiple linear analysis. The result of the analysis showed that seminar and wokshop simultaneously influenced positively and significantly to the interest of learning accounting software, but seminar did not affect the interest of studying accounting software, while wokshop partially had positive and significant effect on interest in learning accounting software.